2002
DOI: 10.1023/a:1015700801579
|View full text |Cite
|
Sign up to set email alerts
|

Cestodes of the family Dilepididae (Cestoda: Cyclophyllidea) from fish-eating birds in Mexico: a survey of species

Abstract: A survey of adults of dilepidid tapeworms (Cyclophyllidea) from piscivorous birds from Mexico is presented on the basis of the taxonomic evaluation of freshly collected and voucher specimens. The following species are reported (first records from Mexico marked with an asterisk): Cyclustera capito (Rudolphi, 1819); *C. ibisae (Schmidt & Bush, 1972); *Dendrouterina ardeae Rausch, 1955; *D. herodiae Fuhrmann, 1912; *D. papillifera (Fuhrmann, 1908); Glossocercus auritus (Rudolphi, 1819); *Neogryporhynchus cheilanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 10 publications
0
20
0
4
Order By: Relevance
“…Recent phylogenetic studies have confirmed its validity and its distinctness from the Dilepididae sensu stricto (Mariaux 1998, Hoberg et al 1999. Therefore, the species previously reported as dilepidids by parasitologists, including the present authors (e.g., Scholz 2001, Scholz and Salgado-Maldonado 2001, Scholz et al 2002a, are considered here to belong to the Gryporhynchidae.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recent phylogenetic studies have confirmed its validity and its distinctness from the Dilepididae sensu stricto (Mariaux 1998, Hoberg et al 1999. Therefore, the species previously reported as dilepidids by parasitologists, including the present authors (e.g., Scholz 2001, Scholz and Salgado-Maldonado 2001, Scholz et al 2002a, are considered here to belong to the Gryporhynchidae.…”
Section: Introductionmentioning
confidence: 54%
“…The following specimens have been studied (for a survey of additional extensive material of gryporhynchids from Eurasia and North America previously studied by the present authors see Scholz et al 1996Scholz et al , 2002a (Joyeux et Baer, 1935) from Tilapia zillii (Gervais), Naivasha Lake, Kenya (IPCAS C-292); 5 specimens of Cyclustera magna (Baer, 1959) from the same host and locality (IPCAS C-293), all collected by P.A. Aloo.…”
Section: Survey Of Species Recordedmentioning
confidence: 99%
“…In addition, there is not an explicit concept about the generic composition of the Gryporhynchidae. We accept as sound the opinion of Scholz and Salgado-Maldonado (2001) and Scholz et al (2002), who preferred to consider the "gryporhynchid" genera within the Dilepididae "until the taxonomy of this group of cyclophyllidean tapeworms is resolved" (Scholz and Salgado-Maldonado 2001).…”
Section: Discussionmentioning
confidence: 89%
“…Additional well-fixed material of dilepidids from the AWP should allow exact identifications and perhaps reveal the presence of several additional species. For example, Scholz et al (2002b) found five different dilepidid species in "Phalacrocorax olivaceus" (= the neotropic cormorant, P. brasilianus) in Mexico.…”
Section: Discussionmentioning
confidence: 99%